The Effect of Workload on Job Stress, Work Motivation, and Employee Performance - Sinambela, Sarton (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to examine and analyze the effect of workload on work stress, motivation and performance of employees. The method used in this research is descriptive method. The object of this research is all employees who worked at Cooperative Mitra Lestari with a population of 75 people. The sampling technique used nonprobability sampling with a sample size of 75 people. The approach used in this research is Structural Equation Model (SEM) analysis tool Smart-PLS.The results showed workload positive and significant effect on work motivation. The workload is positive and significant effect on employee performance. Workloadnegatively affect work stress. Work stress and no significant negative influence on employee performance. Jobmotivation and significant positive effect on employee performance.